A simple measurement method of molecular relaxation in a gas by reconstructing acoustic velocity dispersion. (15th December 2017) - Zhu, Ming; Liu, Tingting; Zhang, Xiangqun; Li, Caiyun
Abstract: Recently, a decomposition method of acoustic relaxation absorption spectra was used to capture the entire molecular multimode relaxation process of gas. In this method, the acoustic attenuation and phase velocity were measured jointly based on the relaxation absorption spectra. However, fast and accurate measurements of the acoustic attenuation remain challenging. In this paper, we present a method of capturing the molecular relaxation process by only measuring acoustic velocity, without the necessity of obtaining acoustic absorption. The method is based on the fact that the frequency-dependent velocity dispersion of a multi-relaxation process in a gas is the serial connection of the dispersions of interior single-relaxation processes. Thus, one can capture the relaxation times and relaxation strengths of N decomposed single-relaxation dispersions to reconstruct the entire multi-relaxation dispersion using the measurements of acoustic velocity at 2 N + 1 frequencies. The reconstructed dispersion spectra are in good agreement with experimental data for various gases and mixtures. The simulations also demonstrate the robustness of our reconstructive method.